ANALISIS KUALITAS PELAYANAN PUBLIK BIDANG PERPUSTAKAAN OLEH DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA PALANGKA RAYA - Muhlis; Jhon Retei Alfrisandi (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2021)
Public service is as any activity undertaken by the government by a number of people who have each of the activities that are beneficial in a collection or unity, and the provision of services (to serve), the purposes of another person or people who have an interest in the organization in accordance with the basic rules and procedures that have been established by the agency, in particular the quality of public services library by the Department of Library and Archives of the City of Palangka Raya.Based on the theory of Zeithaml (1990), in Harbani Pasolong (2011:133), i.e. there are 5 (five), dimensions that must be contained in the service quality perceived by real consumers like, tangible, reliability, responsiveness, assurance, empathy. Researchers also want to see how the quality of public services library in the Department of Library and Archives of the City of Palangka Raya, as well as supporting and inhibiting the library in the Department of Library and Archives of the City of Palangka Raya. The research method used is the descriptive qualitative method to determine how the implementation of the quality services the public library in the Department of Library and Archives of the City of Palangka Raya, as well as to know the supporting and inhibiting in the implementation of the quality services the public library by the Department of Library and Archives of the City of Palangka Raya. Data collection techniques used were observation, in-depth interviews, and documentation. Based on the results of the research obtained by the researcher in conducting the research library in the Department of Library and Archives of the City of Palangka Raya in the Quality of Public Services, it is still not maximized, it can be seen from the reliability, responsiveness, and assurance from employee service in the library Department of Library and Archives of the City of Palangka Raya. Expected the training to employee service in the library Department of Library and Archives of the City of Palangka Raya in order to improve the quality of service be in public that already exist today